Knowledge Management Strategy to Improve Lecturer Research Performance at College of Economics - Dhimas Buing Rindi Widra Yato; Singmin Johanes Lo (Dinasti International Journal of Education Management And Social Science, 2023)
Knowledge management is one of the main methods of a higher education institution to develop knowledge-based innovation. During the COVID-19 Pandemic, research performance in the social and economic fields in Indonesia decreased by 433%. One of the Colleges of Economics (STIE) in Tangerang is currently making changes to improve the research performance of lecturers who have various constraints due to the competence of existing lecturers, the current wage strategy, and low motivation. This study aims to find out how knowledge management processes consisting of knowledge discovery, knowledge capture, knowledge sharing, and knowledge application are used for lecturers’ research; the role of the knowledge management component consisting of people, process, and technology in each process; constraints in the knowledge management process; as well as knowledge management strategies are the things that can be implemented by the College of Economics. The research method used is qualitative research using the NVivo software analysis tool for Windows. The results of this study are in the form of a four-stage strategy consisting of the formulation, implementation, monitoring, and evaluation stages that can be implemented by the College of Economics to support efforts to improve lecturer research performance. The formulation stage includes guaranteeing the availability and clarity of policies, road maps and research SOPs, as well as a reward & punishment system. The implementation stage is to provide a tool in the form of a data repository for lecturers to carry out knowledge management processes, and ensure that leaders set an example by playing an active role in using the tool. The monitoring and evaluation phase is used to ensure that ongoing implementation does not deviate from the plan, and to ensure that the strategies provided are useful for improving lecturer research.